Hunting for metals using XQ-100 Legacy Survey composite spectra. Issue 1 (4th September 2018) - Perrotta, S; D'Odorico, V; Hamann, F; Cristiani, S; Prochaska, J X; Ellison, S L; Lopez, S; Cupani, G; Becker, G; Berg, T A M; Christensen, L; Denney, K D; et al.
ABSTRACT: We investigate the N v absorption signal along the line of sight of background quasars, in order to test the robustness of the use of this ion as the criterion to select intrinsic (i.e. physically related to the quasar host galaxy) narrow absorption lines (NALs). We build composite spectra from a sample of ∼ 1000 C iv absorbers, covering the redshift range 2.55 < z < 4.73, identified in 100 individual sight lines from the XQ-100 Legacy Survey. We detect a statistically significant N v absorption signal only within 5000 km s −1 of the systemic redshift, z_em . This absorption trough is ∼ 15 σ when only C iv systems with N (C iv ) > 10 14 cm −2 are included in the composite spectrum. This result confirms that N v offers an excellent statistical tool to identify intrinsic systems. We exploit stacks of 11 different ions to show that the gas in proximity to a quasar exhibits a considerably different ionization state with respect to gas in the transverse direction and intervening gas at large velocity separations from the continuum source. Indeed, we find a dearth of cool gas, as traced by low-ionization species and in particular by Mg ii, in the proximity of the quasar. We compare our findings with the predictions given by a range of cloudy ionization models and find that they can be naturally explained by ionization effects of the quasar.